Narrative review on embracing advances in technology for clinical teaching and learning in audiology: opportunities delivered by COVID-19 to the South African academy - Khoza-Shangase, Katijah (Frontiers in Education, 2025)
BackgroundThe COVID-19 pandemic precipitated a global shift in education and healthcare delivery, including the field of audiology. In South Africa, the sudden transition to remote learning and tele-healthcare posed unique challenges, particularly given existing resource constraints and technological inequities. This review synthesizes the current literature on the use of technological advancements for clinical teaching and learning in audiology, identifying the opportunities and challenges introduced by the pandemic.AimThis paper aims to explore the evidence on how advances in technology were embraced for clinical teaching and learning in audiology, with a focus on the South African academic context following the onset of COVID-19.MethodsA narrative review methodology was employed to explore and synthesize a broad range of literature, including peer-reviewed articles, gray literature, and reports on technological advancements in audiology education and clinical practice. The review involved iterative cycles of searching, analysis, and interpretation of available evidence. Themes were identified related to the use of tele-audiology, virtual simulations, and online platforms for professional development, with a focus on the South African context.ResultsFive key themes emerged from the analysis: (1) Embracing tele-audiology for clinical training and service delivery, (2) Utilization of virtual simulations to compensate for in-person clinical training, (3) Challenges and inequalities in access to technology, (4) Shifting to online platforms for continuing professional development (CPD), and (5) The potential for hybrid models in audiology education. While technology offered flexibility and continued learning, significant barriers such as digital infrastructure gaps and regulatory constraints were highlighted.ConclusionThe COVID-19 pandemic accelerated the adoption of technological tools in audiology education and practice in South Africa. Tele-audiology, virtual simulations, and online platforms for CPD were pivotal in maintaining clinical education and service delivery during the pandemic. However, challenges related to access, infrastructure, and training must be addressed to ensure the equitable and sustainable use of these technologies in the future.